Portal vein tumor thrombus of liver metastasis from lung cancer - Ogawa, Ryoko; Kodama, Takahide; Kurishima, Koichi; Kagohashi, Katsunori; Satoh, Hiroaki (Acta medica (Hradec Kralove), 2009)
We report a case of liver metastasis of lung carcinoma with portal vein tumor thrombus (PVTT). Although the primary lesion of lung tumor remained unchanged, the patient rapidly developed wide-spread metastases and formed PVTT of liver metastasis. The primary lesion showed features of mixed Clara and bronchial surface epithelial cell component type adenocarcinoma with small foci of micropapillary pattern. Micropapillary pattern was observed in the metastatic lesions in the liver and PVTT. Micropapillary pattern lung adenocarcinoma may develop rapid metastases and cause PVTT associated with liver metastasis. We should perform a detailed examination to establish correct diagnosis.
Keywords: senioři; nádorové cirkulující buňky; Lung Neoplasms; Liver Neoplasms; žilní trombóza; mužské pohlaví; nádory plic; adenokarcinom; Humans; nádory jater; vena portae; Aged; Portal Vein; Neoplastic Cells, Circulating; Venous Thrombosis; Adenocarcinoma; lidé; Male